Plan de negocio para la comercialización de “edulcorante natural a base de stevia” en el cantón La Maná, provincia de Cotopaxi año 2014 - Moreno Reyes, Pamela Natalia (2016)
This research study aims to determine the feasibility of a business plan for the creation of a producer and marketer of Natural Sweetener Stevia located in Canton La Maná with cantonal coverage initially for the future expand coverage to zonal . The research methods used were induction, deduction, analysis, synthesis and research techniques such as observation and surveys of potential consumers which allowed determining the level of demand. The results of this research are summarized in a diagnosis applied to the project environment, where favorable market conditions and obtaining raw materials, on the other hand are significant opportunities and future risks can be controlled is determined. Market research confirms acceptance of the product and an unmet demand for 3042 families for 2014, therefore feasibility has a good chance of success for the implementation of the business plan....